Sex differences and athletic performance. Where do trans individuals fit into sports and athletics based on current research? - Oberlin, D. J. (Frontiers in Sports and Active Living, 2023)
There are well known sex differences in parameters of physical fitness/performance due to changes occurring during sexual development. Thus, many sport and athletic events have regulations separating male and female participants. However, the inclusion or exclusion of transgender individuals in athletics has recently received outsized attention despite relatively few cases of transgender athletes. When determining which athletic gender category trans individuals should be permitted to compete in, it is important to understand the level of physical fitness/performance these individuals possess relative to their cisgender counterparts. Unfortunately, there are few studies investigating this topic, and several complications that confound this research. The current review seeks to discuss sex and gender as concepts, review sex differences in fitness/performance and how they develop, and then, consider how current evidence suggests that trans individuals compare to cis individuals. Finally, this review seeks to offer considerations for whether trans individuals should be excluded from sports and athletics, and how future research should proceed to better understand this marginalized population.